Soil organic carbon enrichment of dust emissions: magnitude, mechanisms and its implications for the carbon cycle. Issue 14 (22nd March 2013) - Webb, Nicholas P.; Strong, Craig L.; Chappell, Adrian; Marx, Samuel K.; McTainsh, Grant H.
ABSTRACT: Soil erosion is an important component of the global carbon cycle. However, little attention has been given to the role of aeolian processes in influencing soil organic carbon (SOC) flux and the release of greenhouse gasses, such as carbon dioxide (CO2 ), to the atmosphere. Understanding the magnitude and mechanisms of SOC enrichment in dust emissions is necessary to evaluate the impact of wind erosion on the carbon cycle. This research examines the SOC content and enrichment of dust emissions measured using Big Spring Number Eight (BSNE) wind‐vane samplers across five land types in the rangelands of western Queensland, Australia. Our results show that sandy soils and finer particulate quartz‐rich soils are more efficient at SOC emission and have larger SOC dust enrichment than clay‐rich aggregated soils. The SOC enrichment ratios of dusts originating from sites with sand‐rich soil ranged from 2·1–41·9, while the mean enrichment ratio for dusts originating from the clay soil was 2·1. We hypothesize that stronger inter‐particle bonds and the low grain density of the aggregated clay soil explain its reduced capacity to release SOC during saltation, relative to the particulate sandy soils. We also show that size‐selective sorting of SOC during transport may lead to further enrichment of SOC dust emissions. Two dust samples from regional transport events were found to contain 15–20% SOC. These preliminary results provide impetus for additional research into dust SOC enrichment processes to elucidate the impact of wind erosion on SOC flux and reduce uncertainty about the role of soil erosion in the global carbon cycle. Copyright © 2013 John Wiley & Sons, Ltd.